2013
DOI: 10.1103/physrevd.88.105014
|View full text |Cite
|
Sign up to set email alerts
|

Resonance mass spectra of gravity and fermion on Bloch branes

Abstract: In this paper, by presenting the potentials of Kaluza-Klein (KK) modes in the corresponding Schrödinger equations, we investigate the localization and resonances of gravity and fermion on the symmetric and asymmetric Bloch branes. We find that the localization properties of zero modes for gravity and fermion in the symmetric brane case are the same, whereas, for the asymmetric brane case, the fermion zero mode is localized on one of the sub-branes, while the gravity zero mode is localized on another sub-brane.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 68 publications
1
51
0
Order By: Relevance
“…Moreover, the zero mode of the equation (19) is not bound on the brane, as showed in figure (4). Thus, we cannot exclude the possibility of tachyonic states [33,38].…”
Section: Massive Modesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the zero mode of the equation (19) is not bound on the brane, as showed in figure (4). Thus, we cannot exclude the possibility of tachyonic states [33,38].…”
Section: Massive Modesmentioning
confidence: 99%
“…The choice of the integration interval z b = 0.1z max does not interfere with the values of the masses to the possible resonance modes [15]. A symmetric brane should result in even and odd solutions ofŪ (z) [38]. Hence we use the initial conditions U (0) = 1 and U (0) = 0 for the even solutions and the conditions U (0) = 0 and U (0) = 1 for the odd solutions [38].…”
Section: Massive Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…3 offer explicit possibilities to implement the hybrid Bloch brane scenario, and the results open up new issues, such as the ones investigated before in the case of the Bloch brane, namely the study of degeneracy and criticality, fermion localization, gauge field localization, and graviton resonances [15][16][17][18][19][20][21][22][23]25,26]. We end our work in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…[14] the authors suggested a brane scenario described by two real scalar fields coupled with gravity, the second field contributing to propitiate internal arrangement, implementing therefore the so-called Bloch brane model. This framework was then explored by several authors in different situations, such as in the study of criticality and degeneracy, fermion localization, gauge field localization, graviton resonances, and so forth [15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%